2019
DOI: 10.20473/j.djmkg.v52.i2.p90-94
|View full text |Cite
|
Sign up to set email alerts
|

The effects of topical application of red pomegranate (Punica granatum Linn) extract gel on the healing process of traumatic ulcers in Wistar rats

Abstract: Background: Trauma-induced ulcers constitute one of the painful abnormalities affecting the oral cavity about which numerous individuals complain. The prevalence of traumatic ulcers (15-30% of cases) is relatively high compared to other oral lesions. Unfortunately, the use of anti-inflammatory drugs classified as steroids can lead to contraindications and serious side effects. Hence, the use of natural ingredients represents an alternative treatment. One such ingredient is red pomegranate containing bioactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 4 publications
0
5
0
4
Order By: Relevance
“…22 Clinical studies performed by several researchers have demonstrated the application of medicinal plants to accelerate the healing process with antiinflammatory effects by their bioactivity abilities to promote wound healing and prevent infection without grave side effects. 23,24,25,26 According to another study, cinnamaldehyde effectively inhibited ox-LDL-induced vascular smooth muscle cells (VSMCs) proliferation, migration, and inflammatory cytokine overproduction, as well as foam cell formation in VSMCs and macrophages. 27 It has been demonstrated in several research with other animals that epithelialization increases.…”
Section: Discussionmentioning
confidence: 99%
“…22 Clinical studies performed by several researchers have demonstrated the application of medicinal plants to accelerate the healing process with antiinflammatory effects by their bioactivity abilities to promote wound healing and prevent infection without grave side effects. 23,24,25,26 According to another study, cinnamaldehyde effectively inhibited ox-LDL-induced vascular smooth muscle cells (VSMCs) proliferation, migration, and inflammatory cytokine overproduction, as well as foam cell formation in VSMCs and macrophages. 27 It has been demonstrated in several research with other animals that epithelialization increases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the lemon pepper gel 5%, 7.5%, and 10% were made by mixing 2.5 grams, 3.75 grams, and 5 grams lemon pepper ethanol extract into 50 grams gel base, respectively. 2 The observations of ulcer size were performed immediately after the injury, 7 th , and 14 th days after the ulcer creation. The ulcer size was measured by vernier caliper in milimeter.…”
Section: Methodsmentioning
confidence: 99%
“…It usually takes 7 to 14 days for traumatic ulcers in the mouth to heal. 2 The objectives of ulcer therapy are to reduce the pain and promote healing, which can be achieved by eliminating the risk factor and applying topical ointments such as topical corticosteroids as the first line of ulcer therapy because they are inexpensive efficacious safe. Inflammatory response, cell proliferation, and production of the extracellular matrix components and the post-healing period, known as remodeling, are the three stages of cell and biochemical processes that are closely linked in wound repair.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic therapy, such as amlexanox and corticosteroids, are usually administered orally (Lewis and Wilson, 2019). However, the mechanism of action of amlexanox is still unknown, and long-term use of corticosteroids has side effects on other organs, such as the liver and the digestive tract, and may increase the incidence of Candida infection in the oral cavity (Abbasi et al, 2016;Hernawati et al, 2019;Lewis and Wilson, 2019).…”
Section: Introductionmentioning
confidence: 99%